Demographic Variability in Fingerprint Patterns - Amna Arooj; Hafiz Muhammad Abbas Malik; Faizan Akram; Hifz Ur Rehman; Kashaf Tul Wuda (Arab Journal of Forensic Sciences & Forensic Medicine)
Fingerprints’ unique patterns are the source of human identification, particularly for forensic investigations. Several studies established an association of fingerprint patterns with demographic variables like age, gender, blood group, and social behavior, but these relations lack statistical evidence. Additionally, a socio-demographic factor, caste, remains unexplored. Here, we report the statistical relationship of demographic factors with fingerprint patterns in Bahawalpur, Pakistan. A quantitative and qualitative approach is utilized to study fingerprint patterns of 500 female individuals. Loop pattern accounts for 64.5%, followed by whorls 27.4% and arches 8.1%, in the sampled population. Among all castes, the loop pattern dominates, followed by whorls and arches. Rajpoot and Malik have slightly higher portions of whorls compared to other castes. A 1-sample t-test shows the variability among demographic factors and indicates that the fingerprint pattern may have some influence on demographic factors. One-way ANOVA highlights that caste may have some significant relation with arches and whorls, while age and blood group show no statistical significance. Pearson correlation and Spearmen Rank’s correlation test give a significant p-value of 0.008 and 0.019, respectively, for caste and fingerprint patterns and support that a significant relationship exists, although weak. These findings emphasize the stability and reliability of fingerprint patterns as biometric identifiers in forensic investigations, especially in a particular demographic region. Future research should implement these findings in a larger population sample and demographic region to understand fingerprint patterns variability further.